Combining dopamine and glucose sensings on paper devices for the metabolic study of neurosecretion - Rémi F. Dutheil; Dabeaurard Tho; Iman Pitroipa; Raphaël Trouillon (Biosensors and Bioelectronics: X)
Glucose, the main source of energy of the human body, and dopamine, a major neurotransmitter, are two analytes widely investigated in the study of the brain. In many pathologies, a dysfunction in their metabolic pathways can be observed, leading to neurological disorders. Better understanding the interplays between secretion and cellular metabolism is critical to better address these diseases. In this study, we study the simultaneous detection of glucose consumption and dopamine secretion using a paper-based electrode (PBE). An electrode made of carbon nanotube-coated paper was functionalized with platinum nanoparticles and glucose oxidase to gain sensitivity towards glucose. Maximal current density (Jmax) and Michaelis–Menten constant (Km) were respectively 12.4±2.0μA.mm−2 and 7.6 ± 1.5 mM for the glucose calibration. The results suggest that dopamine secretion and glucose consumption can be measured in a neuron cell model using the developed paper-based sensor. After stimulating the cells, glucose and dopamine concentration decreased by 1.1 mM and increased by 7.1μM, respectively. In addition, to confirm the sensor’s detection of dopamine secretion, the impact of L-DOPA, a dopamine precursor, was tested. Dopamine secretion increased two-fold after incubation with L-DOPA, while glucose consumption remained unchanged. This opens new opportunities for quantitative, rapid multianalyte sensing of the chemical inputs and outputs of cellular mechanisms with an easy-to-use and affordable device.